2021
DOI: 10.37398/jsr.2021.650610
|View full text |Cite
|
Sign up to set email alerts
|

A Volumetric and Acoustical Study to Explore Interactions between Saline Salts and Fertilizer in view to Control the Salinity of Soil

Abstract: The salinity of soil has great effects on nutrients availability to plants or crops and on the ability of plant roots to absorb nutrients. Because of low productivity problems in the salt affected soils, fertilizers are applied to counteract the conditions which limit the plant absorption of nutrients. Thus the present work is aimed to understand the structural/molecular changes of solute (fertilizer) in solutions (saline salts) which results various solute-solvent, solvent-solvent and ion-solvent interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…6 shows that the increase of Relative Association through concentration recommends that near relation of constituent of molecular and with intermolecular forces the solution. Hence observed that the sequence of rising relative association of Vitamin C in water also in both glucose and glycine in the following manner, Vitamin C+ Glucose + H2O > Vitamin C + Glycine + H2O > Vitamin C + H2O [24]. The graphical values of relative change in adiabatic compressibility are shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…6 shows that the increase of Relative Association through concentration recommends that near relation of constituent of molecular and with intermolecular forces the solution. Hence observed that the sequence of rising relative association of Vitamin C in water also in both glucose and glycine in the following manner, Vitamin C+ Glucose + H2O > Vitamin C + Glycine + H2O > Vitamin C + H2O [24]. The graphical values of relative change in adiabatic compressibility are shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The density is known as the measurement of closely packed material together. The variation of the density with concentration is shown in Fig 2 . From the graph, it is observed that density rises along with rising concentration indicating that the presence of solute-solvent forces is present because of hydrogen bonding between them [11]. The variation of relative association values with concentration and temperature is shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…This rise in the relative Change in adiabatic compressibility along the rise of concentration of glucose in water also in both the salt solutions may assign rising of cohesive forces in the solutions. [12] The Specific Heat Ratio was a special physical quantity that depends on the temperature and density of the fluids and its mixtures. Figure ( 6) convey the variation of specific heat ratio at various concentrations and temperatures.…”
Section: Resultsmentioning
confidence: 99%